The links between pedagogical competence, instructional quality, and mathematics achievement in the lower secondary classroom - König, Johannes; Blömeke, Sigrid; Jentsch, Armin; Schlesinger, Lena; Nehls, Caroline Felske née; Musekamp, Frank; Kaiser, Gabriele (Educational studies in mathematics, 2021)
It is widely assumed that teachers play a key role in providing high-quality learning opportunities to students and fostering students’learning. Yet it is still unclear how specific teacher knowledge facets as part of their professional competence contribute to classroom processes and learning outcomes. Focusing on mathematics education at the secondary level, this study investigates the links between teachers’pedagogical competence (i.e., cognitive pedagogical facets of their professional competence), instructional quality, and students’mathematics achievement. The sample comprises mathematics teacher and student data from 59 classrooms in Germany. Student mathematics achievement was measured across two time points (grade 7 and 8). Teachers’ pedagogical competence was tested using two tests measuring their general pedagogical knowledge (GPK) and situation-specific classroom management expertise (CME). Instructional quality was measured using observational rating data from in vivo rating in mathematics classrooms. Research questions on the relation of teachers’ competence and students’ mathematics achievement were answered using multilevel models. Results from multilevel regression analyses indicate that both GPK and CME predict instructional quality. Direct statistical effects on students’mathematical progress were identified, whereas no indirect statistical effects via instructional quality could be identified. Although teachers’ measured pedagogical competence is not subject-specific, it serves as a significant predictor for cognitive activation as an indispensable part of quality-oriented mathematical teaching and learning processes in the lower secondary mathematics classroom, and it contributes to students’ mathematical progress.